Controlling monopoly power in a double‐auction market experiment. (5th March 2021) - Attanasi, Giuseppe; Boun My, Kene; Guido, Andrea; Lefebvre, Mathieu
Abstract: There is robust evidence in the experimental economics literature showing that monopoly power is affected by trading institutions. In this paper, we study whether trading institutions themselves can shape agents' market behavior through the formation of anchors. We recreate experimentally five different double‐auction market structures (perfect competition, perfect competition with quotas, cartel on price, cartel on price with quotas, and monopoly) in a within‐subject design, varying the order of markets implementation. We investigate whether monopoly power endures the formation of price anchors emerged in previously implemented market structures. Results from our classroom experiments suggest that double‐auction trading institutions succeed in preventing monopolists from exploiting their market power. Furthermore, the formation of price anchors in previously implemented markets negatively impacts on monopolists' power in later market structures.